Human Error Mitigation in The Process of Installing Plastic Body Parts of Electric Motorcycle Products Using The Sherpa and Heart Methods - Setyaji, Bagas Athallah Setyaji; Septiani, Winnie Septiani; Safitri, Dian Mardi Safitri (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2026)
The problem identified in the plastic body installation process of GESITS electric motorcycles is human error committed by operators. These errors include improper installation of parts that create gaps between components, failure to install nuts, bolts, and couplers, and failure to return tools after use. This study aims to reduce the potential for human error by applying the Systematic Human Error Reduction and Prediction (SHERPA) and Human Error Assessment and Reduction Technique (HEART) methods to identify errors and determine appropriate mitigation strategies. Direct observations were conducted on eight operators across four workstations. Interviews with Quality Assurance (QA) and Quality Control (QC) personnel were also conducted to obtain relevant information on product quality issues. The analysis shows that the highest potential error occurs when operators fail to return tools after use, which may result in product scratches or pose safety risks to operators. The second-highest potential error involves improper installation of parts in accordance with standards. Based on the findings, proposed improvements include conducting training and performance evaluations for production personnel, developing QC running check sheets to ensure product quality during assembly, and installing safety and SOP reminder signs to emphasize the importance of returning tools after use.